Assessing the effect of ambiguity in compositionality signaling on the processing of diphones. (May 2018) - Baumann, Andreas; Kaźmierski, Kamil
Abstract: Consonantal diphones differ as to their ambiguity (whether or not they indicate morphological complexity reliably by occurring exclusively either within or across morphemes) and lexicality (how frequently they occur within morphemes rather than across morpheme boundaries). This study empirically investigates the influence of ambiguity and lexicality on the processing speed of consonantal diphones in speech perception. More specifically, its goal is to test the predictions of the Strong Morphonotactic Hypothesis, which asserts that phonotactic processing is influenced by morphological structure, and to clarify the two conceptions thereof present in extant research. In two discrimination task experiments, it is found that the processing speed of cross-morpheme diphones decreases with their ambiguity, but there is no processing difference between primarily cross-morphemic and morpheme-internal diphones. We conclude that the predictions of the Strong Morphonotactic Hypothesis are borne out only partially, and we discuss the discrepancies. Highlights: Ambiguity in signaling morphological complexity affects diphone processing. Speakers have probabilistic knowledge of how often diphone types span morpheme boundaries. Diphones that occur prototypically within morphemes are processed as fast as prototypically cross-morphemic diphones Processing of cross-morphemic diphones is slow if they are ambiguous. Participants can be primed for analyzing diphones in nonce words as spanning a morpheme boundary.